ChemInform Abstract: Amide, Cyclohexenone, and Cyclohexenone—Sordaricin Derivatives from the Endophytic Fungus Xylaria plebeja PSU‐G30. Issue 19 (13th May 2014) - Rukachaisirikul, Vatcharin; Buadam, Sathit; Phongpaichit, Souwalak; Sakayaroj, Jariya
Abstract Two new cyclohexenones, named xylariacyclones A (Ia) and B (Ib), three cyclohexenone—sordaricin derivatives, named xylarinonericins A (IIa), B (IIb), and C (IIc), as well as xylariamide (III) are isolated along with 11 known compounds from the broth extract of the endophytic fungus Xylaria plebeja PSU‐G30.